Manet's The Street Singer and the poets. Issue 2 (3rd April 2018) - Dolan, Therese
Abstract: I claim that Édouard Manet's painting The Street Singer (1862) has ties to Charles Baudelaire's poem "À une mendiante rousse." The poem was included in the 1857 edition of Les Fleurs du mal and became a part of the Tableaux Parisiens in 1861. The young waif who inspired Baudelaire also found herself limned in a poem by Théodore de Banville, celebrated in a song by Pierre Dupont, and painted in oil by Émile Deroy in the mid-1840s at a time when these four men were in close contact with one another in the heady days of their bohemian youth on the cusp of their creative careers. Baudelaire's memories of the formative years of these friendships of the 1840s were resurrected when he took on the commission to write essays on Banville and Dupont for Eugène Crépet's anthology Les Poètes français, conceived in 1859 and published in 1862, the year Manet created his version of a street singer. These texts in all likelihood combined with Manet's own interest in fashion to play a part in his decision to outfit his street singer in attractive attire, but inspiration from Banville's "À une petite Chanteuse des Rues, " Dupont's "La Joueuse de guitare, " and Baudelaire's "À une mendiante rousse" may also have affected Manet's sartorial designs for his painting. I also demonstrate that the discourse surrounding street songs and their aesthetic import proved even more pertinent to Manet's choice of subject as he forged his modernist painting.